New Neotropical and Nearctic species of water beetles in the genera Hydraena Kugelann and Ochthebius Leach, a key to North American genera and subgenera of the family, new distribution records, and a synopsis of ecology, behavior and morphology related to aquatic life (Coleoptera: Hydraenidae) - Perkins, Philip D. (Zootaxa, 2023)
Twenty-six new species of Hydraenidae are described, including new species from Belize (2), Mexico (16), Panama (3), St. Vincent (1), and the U.S.A. (4). High-resolution digital images of the habitus and male genitalia of holotypes are given. New distribution data are provided for 70 species, and new habitus and aedeagal images are given for members of the subgenus Spanglerina: H. (Spanglerina) brevis Sharp, H. (Spanglerina) frondsicola Perkins, and H. (Spanglerina) ingens Perkins. The following new species are described: Hydraena (Holcohydraena) chandleri, H. (Hydraenopsis) belicollis, H. (Hydraenopsis) belilymba, H. (Hydraenopsis) bicandida, H. (Hydraenopsis) canalula, H. (Hydraenopsis) comicala, H. (Hydraenopsis) concatenata, H. (Hydraenopsis) guanajuatoensis, H. (Hydraenopsis) lenticula, H. (Hydraenopsis) multivillosa, H. (Hydraenopsis) panbrevis, H. (Hydraenopsis) panelephanta, H. (Hydraenopsis) pantitillata, H. (Hydraenopsis) pocilla, H. (Hydraenopsis) reducta, H. (Hydraenopsis) saintvincentensis, H. (Hydraenopsis) scintillasolata, H. (Hydraenopsis) spiralis, H. (Hydraenopsis) temascaltepecica, H. (Spanglerina) arcei, Ochthebius (Asiobates) cascadeus, O. (Asiobates) convexus, O. (Asiobates) invictus, O. (Asiobates) shepardi, O. (s. str.) bajaensis, O. (s. str.) explicitus. New distribution records are provided for 70 species. The species status of Ochthebius (Gymnochthebius) falli (Perkins) is reinstated. A very brief synopsis is given of the exocrine secretion delivery system (ESDS) as it relates to the behavior and morphology of hydraenid aquatic life.